The antecedents and impacts of green eProcurement infrastructure: evidence from the Indonesian public sector. (1st January 2013) - Wahid, Fathul
This study aims to understand the factors that affect the implementation process of the eProcurement infrastructure in the Indonesian public sector, and its impacts. The concept of green information systems (IS) decision–making and the concept of the triple bottom line of sustainability were used as lenses. The notion of green IS was extended by incorporating the concept of sustainability. Using an interpretive stance, the study found that legal, technological, and managerial factors affected the implementation of the green infrastructure. The impacts of the green II was well captured by the concepts of the triple bottom line of sustainability: planet (such as reduced use of paper, less frequent trips/less CO 2 emission), people (such as a more transparent procurement process, the inclusion of small– and medium–sized enterprises), and profit (such as cost reduction, faster processes).